1998
DOI: 10.1038/sj.onc.1201661
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell growth inhibition by caveolin re-expression in human breast cancer cells

Abstract: Cancer development is a multistage process that results from the step-wise acquisition of somatic alterations in diverse genes. Recent studies indicate that caveolin-1 expression correlates with the level of oncogenic transformation in NIH3T3 cells, suggesting that caveolin in caveolae may regulate normal cell proliferation. In order to better understand potential functions of caveolin-1 in cancer development, we have studied expression levels of caveolin-1 in human breast cancer cells, and have found that cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
300
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(330 citation statements)
references
References 18 publications
(30 reference statements)
27
300
3
Order By: Relevance
“…Prior studies have suggested that oncogenic transformation results in reduced cellular levels of caveolin (Glenney and Soppet, 1992;Sager et al, 1994;Koleske et al, 1995), and that this reduction probably contributes to a loss of caveolae (Koleske et al, 1995). Lee et al (1998) found that the CAV1 levels were inversely correlated to breast cancer progression in vitro and the overexpression of CAV1 resulted in substantial growth inhibition of breast tumour cells, which normally had no endogenous caveolin expression. Our study confirmed that mRNA level of CAV1 and CAV2 were significantly downregulated in human breast cancer tissues compared to corresponding normal tissues (Po0.001), and that CAV1 and CAV2 mRNA levels were significantly correlated with each other in breast cancer cell lines and tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have suggested that oncogenic transformation results in reduced cellular levels of caveolin (Glenney and Soppet, 1992;Sager et al, 1994;Koleske et al, 1995), and that this reduction probably contributes to a loss of caveolae (Koleske et al, 1995). Lee et al (1998) found that the CAV1 levels were inversely correlated to breast cancer progression in vitro and the overexpression of CAV1 resulted in substantial growth inhibition of breast tumour cells, which normally had no endogenous caveolin expression. Our study confirmed that mRNA level of CAV1 and CAV2 were significantly downregulated in human breast cancer tissues compared to corresponding normal tissues (Po0.001), and that CAV1 and CAV2 mRNA levels were significantly correlated with each other in breast cancer cell lines and tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Loss or reduction of caveolae and of cav-1 expression was ®rst described in NIH3T3 cells transformed by activated oncogenes (Koleske et al, 1995) and more recently, in cell lines derived from breast and lung cancer (Lee et al, 1998;Racine et al, 1999). Based on several observations, it has been suggested that regulation of cav-1 gene expression might be a critical point in maintaining the transformed phenotype and that cav-1 itself might be considered a tumor suppressor gene (Engelman et al, 1998b;Lee et al, 1998).…”
Section: Regulation Of Afr Expression In Cav-1-transfected Igrov1 Cellsmentioning
confidence: 99%
“…Based on several observations, it has been suggested that regulation of cav-1 gene expression might be a critical point in maintaining the transformed phenotype and that cav-1 itself might be considered a tumor suppressor gene (Engelman et al, 1998b;Lee et al, 1998).…”
Section: Regulation Of Afr Expression In Cav-1-transfected Igrov1 Cellsmentioning
confidence: 99%
“…Furthermore, several independent studies have demonstrated a reciprocal interaction between the expression of caveolin-1 and activated components of the ERK1/2 MAP kinase signalling pathway [17][18][19][20]. While, caveolin-1 mRNA and protein has been shown to be present in normal human mammary epithelial cells it has also been reported to be greatly reduced or absent in an extensive range of transformed cells derived from human breast cancers [21][22][23][24]. Caveolin-1 has been proposed as the elusive tumour suppressor protein residing at chromosomal loci 7q31.1, a fragile site frequently deleted in a wide spectrum of human cancers [25].…”
Section: Introductionmentioning
confidence: 99%